2017
DOI: 10.21608/ejss.2017.3715
|View full text |Cite
|
Sign up to set email alerts
|

Response of Wheat Plants to Application of Selenium and Humic acid under Salt Stress Conditions

Abstract: Results showed that soaked wheat grains in different concentrations of mixtures of selenium and humic acid led to increases the percentage of germination as well as length both shoot and root along with their dry matter contents, were also favored total soluble sugars.Results also revealed that used mixtures of selenium and humic acid in saline soil led to increases resistance of plants to salinity conditions, therefore decreasing the content of proline compared to control, in case of wheat grains, the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…It has been previously reported that soaking seeds before planting in Se solution increases the rate of selenium uptake and its quantity in the final crop. 44 Moreover, Se supplementation increases the antioxidant activity of plants. 45,46 This is clearly evident in this study, where the different soaking treatments led to a significant increase in the Se content of dry faba bean seeds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that soaking seeds before planting in Se solution increases the rate of selenium uptake and its quantity in the final crop. 44 Moreover, Se supplementation increases the antioxidant activity of plants. 45,46 This is clearly evident in this study, where the different soaking treatments led to a significant increase in the Se content of dry faba bean seeds.…”
Section: Discussionmentioning
confidence: 99%
“…В інших дослідженнях використання комплексу гумінових речовин, амінокислот та мікроелементів сприяло збільшенню врожайності та поліпшенню показників якості зерна ячменю без істотного впливу на вміст вуглеводів [15]. Гумінові речовини суттєво сприяють зменшенню вмісту важких металів у ґрунті та у продукції зернових культур [16,17].…”
Section: вступunclassified